Penegakan Hukum terhadap Pelaku Tindak Pidana Pertambangan Batu Hias Ilegal di Indonesia - Ahmad Jalaludin Arrodli; Suwari Akhmaddhian (Savana, 2025)
This study aims to analyze law enforcement against the crime of illegal ornamental stone mining, specifically based on a case study of Decision Number 40/Pid.Sus/2024/PN Mna at the Manna District Court. This study uses a normative juridical method by examining Decision Number 40/Pid.Sus/2024/PN Mna and Law Number 4 of 2009 concerning Mineral and Coal Mining. The analysis shows that law enforcement officials have taken firm action by imposing penalties on perpetrators who violate the rules. However, there are obstacles in law enforcement due to low public awareness, limited equipment, and weaknesses in the legal structure and culture in the community. The conclusion states that law enforcement needs to be strengthened through licensing system reform, public education, and more effective supervision to prevent future violations. Suggestions Strengthening cooperation between law enforcement officials and the community, Legal education about the importance of mining permits, Policy reforms that expedite and simplify the processing of mining permits.